AKIBAT HUKUM DALAM PEMALSUAN SURAT TERHADAP TINDAK PIDANA PERTANAHAN PADA PENDAFTARAN TANAH - Nazilah Maghfiroh; Sri Setyadji (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Land registration is a series of activities carried out by the government regularly and continuously. Includes processing, data collection, accounting and maintenance of factual and legal data in the form of maps and inventories of land and residences, as well as issuing certificates of land rights with ownership rights and existing residential units in accordance with Government Regulation No. 24 of 1997. The study discusses the legal consequences of falsifying land registration documents using a normative, juridical, and a statutory, and conceptual approach. The study results show that there is an imbalance between the amount and area of ??available land, which does not increase, so that the need for community use increases, causing land to become very important, leading to state interference through officials in the land law order. The forgery of the letter is part of an effective concentration on sensitive legal issues or the absence of existing regulations in Indonesia. The crime of forging letters is endless, all of them are listed in Article 263 of the Criminal Code. Facts prove that there are still many rights of every person that some letter makers ignore, causing losses